Adverse events associated with sodium glucose co-transporter 2 inhibitors: an overview of quantitative systematic reviews - Ryan Pelletier; Kelvin Ng; Wajd Alkabbani; Youssef Labib; Nicolas Mourad; John-Michael Gamble (SAGE Publishing, 2021)
Background: Multiple published quantitative systematic reviews have reported on adverse events associated with the use of sodium glucose co-transporter 2 (SGLT-2) inhibitors in patients with type 2 diabetes mellitus. Aims: To summarize and appraise the quality of evidence from quantitative systematic reviews assessing adverse events of SGLT-2 inhibitors. Methods: We searched PubMed, EMBASE and the Cochrane Library for quantitative systematic reviews assessing SGLT-2 inhibitor safety. Two reviewers extracted data and assessed methodological quality using the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2) tool. Main outcomes included pooled and single study point estimaates (in the absence of pooled estimates) with corresponding 95% confidence intervals (CIs) of SGLT-2 inhibitors versu s placebo or active comparators for genitourinary infections, volume depletion, acute kidney injury, bone fractures, diabetic ketoacidosis, lower limb amputations, cancers, and other notable adverse events. Results: Out of 1289 citations screened, 47 reviews assessed SGLT-2 inhibitor safety, of which 35 were of low quality. Canagliflozin, dapagliflozin and empagliflozin were consistently associated with an increased risk of genital tract infections versu s placebo (point estimates ranged from 2.5 to 9.8) and other antihyperglycemic agents (point estimates ranged from 2.7 to 12.0). Canagliflozin and dapagliflozin were associated with an increased risk of diabetic ketoacidosis. Canagliflozin was the only agent associated with an increased amputation risk; however, this was driven by results from a single trial program. Dapagliflozin was the only agent that exhibited a statistically significant increased risk of urinary tract infections. Empagliflozin was associated with a statistically significant increased risk of bladder cancer; however, this finding was susceptible to detection bias. None of the agents were associated with a statistically significant increased risk of acute kidney injury, or bone fractures compared to placebo or mixed (active or placebo) comparators. Upper 95% CI limits do not rule out clinically meaningful outcomes. Conclusion: The majority of quantitative systematic reviews reporting on adverse events of SGLT-2 inhibitors were of low methodological quality. Despite almost 50 quantitative systematic reviews published on the safety of SGLT-2 inhibitors, clinicians are still left uncertain of the risks of important adverse effects. Plain Language Summary SGLT-2 iInhibitor side effects: overview of reviews Many published systematic reviews have reported on side effects associated with the use of sodium glucose co-transporter 2 (SGLT-2) inhibitors in patients with type 2 diabetes. We aimed to summarize and appraise the quality of evidence from quantitative systematic reviews assessing side effects of SGLT-2 inhibitors. Using the Assessment of Multiple Systematic Reviews 2 (AMSTAR 2) tool, two authors extracted data and assessed the methods of included reviews. Main outcomes included reported pooled and single study point estimates for several SGLT-2 inhibitor side effects such as genital infections, bone fractures, lower limb amputations, increased blood acidity, among others. Of the reviews included in our study, 35 of the 47 reviews assessed were of low quality. Canagliflozin and dapagliflozin were associated with an increased risk of blood acidity in a 2020 review. Canagliflozin was the only agent associated with an increased amputation risk; however, this was driven by results from a single trial program. Dapagliflozin was the only agent that exhibited a significantly increased risk of urinary tract infections. Empagliflozin was associated with an increased risk of bladder cancer; however, this finding was susceptible to bias. None of the agents were associated with an increased risk of kidney injury or bone fractures.